Answer:
-8
Step-by-step explanation:
f(x)=3x-5
f(-1)=3(-1)-5=-3-5=-8
Answer: 32
Step-by-step explanation:
First, find the lowest common denominator. That is 12. You only have to change 3/4 into 12ths.
3/4 = 9/12
11/12 – 9/12 = 2/12 = 1/6
Answer:
12x -y = -87
Step-by-step explanation:
You can start with the 2-point form of the equation of a line and manipulate it to give you the standard form.
y = (y2 -y1)/(x2 -x1)(x -x1) +y1
y = (-9 -3)/(-8 -(-7))(x -(-7)) +3
y = (-12/-1)(x +7) +3
y = 12x +84 +3
-12x +y = 87 . . . . . subtract the x-term
12x -y = -87 . . . . . . make the leading coefficient positive (per standard form)